Epidemiological investigation of foot-and-mouth disease outbreaks in a Vietnamese bear rescue centre - Ludi, Anna B.; Baker, Hannah; Sanki, Rachel; De Jong, Rosanne M. F.; Maryan, Julie; Walker, Martin; King, Donald P.; Gubbins, Simon; Limon, Georgina; Officer, Kirsty (Frontiers in Veterinary Science, 2024)
Foot-and-mouth disease (FMD) outbreaks affecting Asiatic black bears (Ursus thibetanus) and a Malayan sun bear (Helarctos malayanus) were previously reported in 2011 in two housing facilities at a Vietnamese bear rescue centre. In this study, demographic data of all animals housed in the centre at the time of the outbreaks (n=79) were collected. Blood samples drawn from 23 bears at different timepoints were tested for FMDV-specific antibodies targeting using a non-structural protein (NSP) ELISA and by virus neutralisation test (VNT). The relationship between seroconversion and clinical signs was explored and epidemic curves and transmission diagrams were generated for each outbreak, where FMD cases were defined as animals showing FMD clinical signs.Outbreak-specific attack rates were 18.75% and 77.77%, with corresponding basic reproduction numbers of 1.11 and 1.92, for the first and second outbreaks, respectively. Analyses of risk factors showed that after adjusting for sex there was strong evidence for a decrease in odds of showing clinical signs per year of age. All samples collected from bears before the outbreak tested negative to NSP and VNT. All cases tested positive to VNT following onset of clinical signs and remained positive during the rest of the follow up period, while only 6 out of 17 cases tested positive to NSP after developing clinical signs. Six animals without clinical signs were tested post outbreaks; five seroconverted using VNT and three animals were seropositive using NSP ELISA. This study provides initial epidemiological parameters of FMD in captive bears, showing that FMDV is easily spread between bears in close proximity and can cause clinical and subclinical disease, both of which appear to induce rapid and long-lasting immunity.